Physical Stability Test of Ethanol Extract Cream of Bajakah Wood as Topical Antiaging Cream - Prasetyorini, Budi Eko; Kusumawardani, Arie; Ellistasari, Endra Yustin (Syntax Literate, 2022)
The barakah ethanolic extract (Spatholobus littoralis Hassk) contains antioxidants that function as antiaging. The use of barakah wood ethanolic extract cream as a cosmetic preparation requires a long preparation time, so it is necessary to formulate a preparation that is practical and durable in storage. Cream components affect the physical stability of the preparation. Physical stability tests need to be carried out to ensure the quality, safety, and benefits of the cream meet the expected specifications and are stable during storage. This study aims to make the physical stability of the formulation of the cream preparations of barakah wood ethanol extract at concentrations of 7.5%, 15%, and 30%. The design of this study was an experimental laboratory. The stability test was carried out using the cycling test method for 6 cycles by re-testing its physical properties. Physical evaluation includes organoleptic tests, homogeneity, pH, dispersion, and adhesion. Preparation of cream formula 7.5%, 15%, and 30% of the results of testing physical properties (cycle 0) namely organoleptic test (smell: typical of wood; color: dark brown; texture: semi-solid), homogenity (homogeneous arrangement), pH F1, 2 and 3 p = 0.524; 0.350 and 0.745 adhesion F1, 2 and 3 p = 0.209; 0.207 and 0.377 spreadability F1, 2 and 3: p = 0.690; 0.207 and 0.395 the results of statistical values in formula 1, 2 and 3 which show the value of Sig(2-tailed) where this value is p > 0.05 which means there is no significant difference before and after the cycling test. In the cream stability during the cycling test (cycles 1-6) there was no significant difference. There was no statistically significant difference in any physical evaluation of the cream stem ethanolic extract barakah 7.5%, 15%, and 30% so the three concentrations of cream were stable creams.